OIL PRICE SHOCK AND ECONOMIC GROWTH: EXPERIENCE OF CEMAC COUNTRIES - BESSO, Christophe Raoul; FEUBI PAMEN, Erick Patrick (Theoretical and Practical Research in Economic Fields, 2017)
The objective of this paper is to evaluate the impact of oil shocks on the growth rate of Growth Domestic Product (GDP) in CEMAC countries. We use a panel VAR model approach to the variation of the real GDP growth rate, oil price inflation rate and money supply between 2000 and 2015. Our main results show that CEMAC countries mostly depend on oil pension. Consequently, the analysis of impulsion response functions and the decomposition of variance show that, the shock on oil price negatively affects the growth rate of the GDP. We then suggest CEMAC countries to diversify their production, the destination of their exports and the sources of budgetary income or takings.